Las nuevas formas de materialización de la libertad de expresión y la vulneración del derecho a la intimidad de la persona - Rojas Guanilo, María Cecilia (2015)
The purpose of the research is based on the infringement of the right to privacy of the individual, because of the new forms of realization of freedom of expression generated by technological and computer advances amid a regulatory scheme that becomes ineffective and operating in their supervisory actions, monitoring and control of private and intimate information disclosed to handle unauthorized network Internet mediating the use of tools such as Facebook, twitter, whatsapp, Ircap and the like, as well as that which is disseminated in pseudo journalistic content programs. Methodologically, it has worked with a sample population of 95 units of analysis (45 criminal, constitutional and civil proceedings 10 litigators 05 judges, 10 lawyers, 05 journalists, 10 students of law, citizens 10), statistically selected from a total population consisting of 380 units of analysis. Processing the data, it has been in short, to assert that the infringement of the right to privacy of the individual is surmountable in both -through creation or implementation of a reformed system of care and protection of transgressions of law to achieve privacy based on the exercise of the right to freedom of expression. In this sense, we present our recommendations which include a proposal to amend the constitutional provision to achieve effectiveness in the protection of its rights under our Constitution. Also, it is recommended that the criminalization of offenses containing as legally protected right to privacy against the violations fostered by the media arising from the exercise of freedom of expression.